Numerical Study of Cavitating Flows around a Hydrofoil with Deep Analysis of Vorticity Effects - Li, Shande; Zhong, Wen’an; Yu, Shaoxing; Wang, Hao (Fluid dynamics & materials processing, 2025)
This paper aims to numerically explore the characteristics of unsteady cavitating flow around a NACA0015 hydrofoil, with a focus on vorticity attributes. The simulation utilizes a homogeneous mixture model coupled with a filter-based density correction turbulence model and a modified Zwart cavitation model. The study investigates the dynamic cavitation features of the thermal fluid around the hydrofoil at various incoming flow velocities. It systematically elucidates the evolution of cavitation and vortex dynamics corresponding to each velocity condition. The results indicate that with increasing incoming flow velocity, distinct cavitation processes take place in the flow field.